On the Diversity of Linguistic Evidence for Conceptual Metaphor - Górska, Elżbieta (Studia Anglica Posnaniensia, 2010)
In this article my main concern is the linguistic evidence for the view that metaphor is conceptual in nature. Since the fact that there is a great diversity of linguistic evidence for patterns of metaphorical thought has been, by and large, not emphasized enough, I overview a variety of such evidence, which can be derived from the study of different aspects of meaning within a particular language, crosslinguistically, and at a metalinguistic level. However, in itself the variety of linguistic evidence, even though it speaks very strongly for the idea that metaphor is conceptual in nature, is not sufficient to justify it. Therefore, recognizing the fact that claims about our conceptual system which are based on linguistic analyses alone remain within the "language - thought - language" circle, the article discusses also some kinds of nonlinguistic evidence for conceptual metaphors. Psycholinguistic research on metaphorical reasoning is presented as a major source of such nonlinguistic verifications. Drawing on Daniel Barenboim's BBC Reith lectures of 2006, it is also argued that convergent evidence from language and music may serve to break open the "language - thought - language" circle.